Análisis de la indización practicada en la revista. Pedagogía Social (1998-2003) - Sánchez Valle, Ignacio (Revista Complutense de Educación, 2007)
Social Sciences reviews have lately made an effort to increase their standards. Two of the main criteria of LATINDEX refer to indexing (key words). This work is based on present scientific Documentation and on Pedagogical Documentation and it describes the indexing made by the Pedagogía Social review from 1998 to 2003 is described. Proposals are made in order to optimize processes of indexing. The idea that each science should care about its own terminology is defended. From the present international context of higher education which affects Pedagogy (European Space of Higher Education and Latin American Space of Higher Education), the idea of promoting further the use of the European Thesaurus of Education in processes of indexing is advocated.